Interpersonal metadiscursive features in contemporary Islamic friday sermon - Mahmood, Israa Ismaeel; Mohd Kasim, Zalina (Penerbit UKM, 2019)
The Islamic Friday sermon is one of the most influential and educational means that plays an effective role in shaping the attitudes and beliefs of the individuals and society at large. Through the use of a powerful language, religious orators affect congregations emotionally and intellectually to achieve the Friday sermon’s purposes. This paper examines how religious orators influence their listeners through the deployment of interactive and interactional metadiscourse features. The interpersonal metadiscourse is operated as framework to realize sermons as a form of social engagement, since it considers the crucial role of the use of discourse to manage both: the social relationship, and the organization of texts. Hyland's (2005) model of metadiscourse was adopted to analyse 30 transcriptions of Islamic Friday sermons delivered in the English language. The findings revealed that metadiscourse resources are used extensively, and that the orators rely more on the use of the interactional resources to achieve their persuasive aims. The findings will give insights on how metadiscourse markers can be effectively used to construct a persuasive context whether in religious discourse or other discourses such as spoken discourse. It gives meaningful hints to the students of religious schools about how to use metadiscourse features in formulating the sermon.